BRIDGING PUBLIC POLICY AND DEFENSE STRATEGY TO COMBAT HYBRID WARFARE: AN ANALYTICAL STUDY ON NATIONAL SECURITY - Sawlani, Dhiraj Kelly; Supriyadi, Asep Adang (Jurnal Praksis dan Dedikasi Sosial, 2024)
In the digital age, hybrid warfare has emerged as a multidimensional threat that combines conventional military tactics with cyberattacks, disinformation, economic pressure, and covert operations. This research examines the urgent need for policy integration between national defense and public policy in responding to these evolving threats. The study employs a national security analysis framework to explore how synergy between defense institutions and public sector agencies can enhance resilience against hybrid attacks. By analyzing empirical cases such as the Russia-Ukraine conflict and cyber intrusions targeting critical infrastructure, the study identifies core vulnerabilities in siloed governance structures and uncoordinated response mechanisms. Key findings highlight the importance of integrating military strategies with cyber defense, economic resilience, and public awareness campaigns. National defense must extend beyond physical readiness to encompass advanced intelligence systems, digital security infrastructure, and public engagement in countering disinformation. Simultaneously, public policy must prioritize digital literacy, economic sovereignty, and institutional cooperation to ensure a whole-of-nation response. The paper recommends establishing a centralized national command for hybrid threat mitigation, enhancing early warning systems, and fostering multi-sector partnerships involving government, private tech companies, and civil society. The success of NATO’s hybrid warfare strategy integration offers a comparative model for countries like Indonesia. Ultimately, this study argues that confronting hybrid warfare demands a seamless convergence of defense and public governance mechanisms, transforming fragmented security protocols into an adaptive and united front.